(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
In the last year, educational experiences have become increasingly challenging due to teaching classes remotely. For this reason, it has been necessary to develop educational strategies that accompany the use of new technologies to maintain student interest. One of these methodolo- gies is gamification, implemented in school environments more frequently due to the pandemic and whose impact on student motivation and engagement needs to be explored. The literature shows that student participation in these contexts should be increased when applying this methodology, where teachers can also provide greater support. This research proposes improving these aspects by developing a gamification strategy that can be easily replicated in other environments. This study was carried out for a chemistry course at a university in central Mexico. This proposal details the short-, medium-, and long-term bonuses which stimulated and motivated students and achieved specific objectives. We also present the quantitative results of a questionnaire applied to 48 engi- neering students to identify their perceptions of how gamification could increase motivation and engagement in learning the subject of chemistry. In addition, pre- and post-knowledge tests were applied to determine whether there were changes in the learning outcomes. The results indicated that gamification increased student motivation and engagement, improved attitudes, promoted ac- tions such as keeping the camera on during lectures and regular attendance, and improved student grades. This study fills the need for planning strategies to help improve student motivation in online classes and proposes an instrument to measure the results. It can be helpful to those interested in applying or adapting it in other disciplines.